Crime scene photography - Robinson, Edward M. (Academic Press/Elsevier, 2016)
Crime Scene Photography, Third Edition, covers the general principles and concepts of photography, while also delving into the more practical elements and advanced concepts of forensic photography. Robinson assists the reader in understanding and applying essential concepts in order to create images that are able to withstand challenges in court.